Analisis Determinan Disparitas Pendapatan di Provinsi Sumatera Utara - Fadillah Sanita Harahap; Erlina Erlina; Rujiman Rujiman (Jurnal Serambi Engineering, 2020)
Development in principle is to create changes in a better direction which includes changes in economic structure, creating growth, social change, reducing or eliminating poverty, reducing disparity and overcoming the problem of unemployment. This study aims to analyze the effect of poverty, unemployment, Human Development Index (IPM) and Regional Original Income (PAD) on income disparity (VW) in North Sumatra Province. The results/Inequality condition in North Sumatra Province shows a decreasing pattern which means income disparity/inequality is getting smaller and more evenly distributed. Judging from the average Williamson Index in the western region has the smallest Williamson Index compared to the eastern region of North Sumatra, the poverty variable (POV) has a negative and significant effect on income, i.e. if POV increases, VW decreases. Unemployment Variable (TPT) has a positive and significant effect on VW, namely if TPT increases, VW increases. The Human Development Indexes variable (HDI) has a positive and significant effect on VW. If the HDI increases, the VW increases, and the Regional Original Income (PAD) has a negative and significant effect on VW, if the PAD increases, the VW decreases.